Transformative Competencies in the Big Five Personality Taxonomy: Literature Review of Individual Development through Guidance and Counseling - Novi Sylvia (Universitas Negeri Malang, 2025)
This study aims to analyze the relationship between transformative competencies and the Big Five personality taxonomy through a systematic literature review and explores its implications for guidance and counseling services. Data were collected from scholarly journals relevant to the Big Five personality and their associations with transformative competencies. Transformative competencies involve reconciling tensions and dilemmas, taking responsibility, and creating new value—critical skills for students navigating the digital era and Society 5.0. The Big Five personality model classifies traits into five dimensions: extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience, each influencing cognitive, emotional, and behavioral responses. Findings indicate that each Big Five dimension contributes uniquely to transformative competencies. Conscientiousness and openness to experience are linked to structured problem-solving and innovation, while agreeableness fosters empathy and conflict resolution. Extraversion enhances collaboration and leadership, whereas neuroticism, when managed effectively, supports resilience and emotional regulation. Strengthening specific personality traits through targeted guidance and counseling interventions can optimize transformative competencies development. By integrating personality-based counseling strategies, educators can foster holistic student growth, ensuring adaptability for academic, personal, and professional success.